Measurement of cardiac muscle relaxation in hypothyroidism. Issue 6022 (5th June 1976) - Manns, J J; Shepherd, A M; Crooks, J; Adamson, D G
Abstract : The isovolumetric relaxation time of the left ventricle (IRT) in 20 hypothyroid patients (133 +/- (SE of mean) 4 ms) was significantly longer than that in 23 normal subjects (95 +/- 3 ms). During a trial of thyroxine replacement the IRT in 12 hypothyroid patients fell from 143 +/- 4 ms to 107 +/- 4 ms. The IRT seems to be a useful index of end-organ function in hypothyroidism.